Negotiating new ways of developing writing in disciplinary spaces: The changing role of writing consultants at the Wits School of Education Writing Centre - Kadenge, Emure; Dison, Laura; Kimani, Wacango; Namakula, Halima (Stellenbosch Papers in Linguistics Plus, 2019)
Writing centres in South African universities have historically been poorly recognised structures in higher education, and have largely been considered as “asides” to the core functions of the university. This lack of acknowledgement has seen writing centres occupying demeaning physical spaces within universities which has had a negative impact on the full potential of writing centre work. This narrative study focuses on the experiences of three postgraduate writing consultants, and reports on the ways that the Writing Centre at the Wits School of Education (WSoE) has exerted agency in order to move from a marginalised position in a school of education to reach students and become more responsive to their needs. While being proactive has yielded many teaching and learning gains at the WSoE, the Writing Centre has also had to contend with various personal and operational tensions such as deficit perceptions from both staff and students, and unrealistic expectations of students that their writing problems will be solved instantly. These challenges, however, have created opportunities for growth of the Writing Centre as it has developed new pathways for consultants in the shift from generic writing consultations to content-specific writing development. The changed model has had implications for the training and pedagogies of writing centre consultants as well as for their identity as students and mentors. This article provides insights into how writing centres can use their agency to occupy more meaningful spaces and places within universities, and enhance academic literacy support whilst simultaneously providing writing consultants with opportunities to grow their scholarship.